Pengaruh Bantuan Asing, Investasi Asing Langsung dan Keterbukaan Perdagangan terhadap Pembangunan Manusia di Indonesia - Mentari Dewi Putri; Maizul Rahmizal (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the influence of foreign aid, foreign direct investment and trade openness on human development in Indonesia. This study uses secondary data in the form of time series sourced from the World Bank, UNDP and OECD from 1990 to 2022. The variables in this study consist of independent variables, namely foreign aid, Foreign Direct Investment and trade opennes, while the dependent variable is the human development. This study uses the ECM (Error Correction model) analysis model. The results of the study show that: (1) In the short term, foreign aid has a significant positive effect on human development in Indonesia, Foreign Direct investment has a positive and insignificant effect on human development in Indonesia while trade opennes has a negative and insignificant effect on human development in Indonesia. (2) In the long term, foreign aid has a positive and insignificant effect on human development in Indonesia, while Foreign Direct investment and trade opennes have a positive and insignificant effect on human development in Indonesia.